2013
DOI: 10.1093/geront/gnt093
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perceived Filial Obligation Norms Among Coresident Family Caregivers in Japan

Abstract: Purpose of the Study: Japan introduced a nationwide long-term care insurance (LTCI) system in 2000, making long-term care (LTC) a right for older adults regardless of income and family availability. To shed light on its implications for family caregiving, we investigated perceived filial obligation norms among coresident primary family caregivers before and after the policy change. Design and Methods: Descriptive and multiple regression analyses were conducted to examine changes in perceived filial obligation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 41 publications
(68 reference statements)
1
40
1
1
Order By: Relevance
“…However, such traditional norms have been changing in Japan in recent years (e.g., Tsutsui, Muramatsu and Higashino, 2014), and indeed, Hanaoka and Norton (2008) find that the role of daughters-in-law in parental care is becoming less important than that of unmarried children. The findings of this study adds another dimension to these existing studies in that a more adverse effect of informal parental care is found on the subjective well-being of unmarried caregivers than that of married caregivers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such traditional norms have been changing in Japan in recent years (e.g., Tsutsui, Muramatsu and Higashino, 2014), and indeed, Hanaoka and Norton (2008) find that the role of daughters-in-law in parental care is becoming less important than that of unmarried children. The findings of this study adds another dimension to these existing studies in that a more adverse effect of informal parental care is found on the subjective well-being of unmarried caregivers than that of married caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…Arai and Ueda (2003) similarly find that the LTCI system has helped change caregivers' attitudes and that more caregivers have come to believe that society must look after the elderly since the launch of the LTCI system. Further, Tsutsui, Muramatsu and Higashino (2014) show that declines in filial obligation were more prominent in the dimension of physical support, which the LTCI covers, than in financial and emotional support dimensions.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…KBB with fewer expectations for their children to take care of themselves may intend to go to LTC facilities as well as have better relationship with their adult children. Recent literature often found the declined norm of filial obligation among adult children in Asian countries (Tsutsui et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The results indicate the increasing importance of a new caregiving role for adult daughters to older Korean immigrant parents and a shift from dutybased traditional filial piety to need-based practical support (Eun, 2003;Hashimoto & Ikels, 2005;Ikels, 2004;Jeon et al, 2013;Koyano, 2003;Lee & Jin, 2013;Lee & Yoon, 2011;Mao & Chi, 2011;Tsutsui et al, 2014). In addition, relationships with adult daughters, in general, may be qualitatively different in ways that benefit parents, emphasizing greater emotional closeness and contact, compared to the more duty-based and possibly more distant or formal relationships with sons and their wives (Pillemer & Suitor, 2014).…”
Section: Discussionmentioning
confidence: 99%